Ligation of the intersphincteric fistula tract (LIFT): a sphincter-saving technique for fistula-in-ano - Mohamed Sidek , Ahmad Shanwani; Md Nor, Azmi; Mohamed Kamil, Nil Amri (Springer Verlag, 2010)
PURPOSE: This study was designed to assess the total anal sphincter–saving technique of ligating the intersphincteric fistula tract for the treatment of fistulain-ano. METHODS: We performed a prospective observational study of patients with fistula-in-ano treated with the ligation of the intersphincteric fistula tract technique from May 2007 through September 2008. All patients had fistulas arising from cryptoglandular infections. Recurrence rate, healing time, and morbidities related to the procedure were determined with a standard followup protocol. RESULTS: Forty-five patients with transsphincteric (n 33) or complex (n 12) fistulas were included in the study. Five patients (11.1%) had recurrent fistula-in-ano after prior surgery using other recognized treatment procedures. The median age was 41.5 (range, 27–56) years; median follow-up, 9 (range, 2–16) months. Primary healing was achieved in 37 patients (82.2%), with a median healing time of 7 (range, 4–10) weeks. Eight patients (17.7%) had recurrence of fistula between 3 and 8 months after the operation. No clinically significant morbidity was noted in any of the 45 patients. CONCLUSIONS: The ligation of the intersphincteric fistula tract technique for fistula-in-ano surgery, which aims at total anal sphincter preservation, appears to be both safe and easy to perform, with encouraging early outcomes.